Wishmaster 2: Evil Never Dies (199 - Sholder, Jack.; Divoff, Andrew; Paul Johansson; Holly Fields; Bokeem Woodbine; Carlos Leon; Robert LaSardo; Oleg Vidov; Tommy 'Tiny' Lister; Chris Weber; Al Foster; Vyto Ruginis; et al. (USA Artisan Entertainment)
The evil Djinn is awakened by a female thief, Morgana, during a botched robbery. He takes credit for the crime, letting himself be put into prison so that he can offer twisted wishes to prisoners in return for their souls. If Morgana asks him for three wishes, then his race, the Djinn, can take over Earth, killing all humanity.
During a failed art heist, the Djinn is once again liberated. This time, to complete the 1001 wishes that he needs before the final 3, he lets himself go to prison, where he starts his evil reign twisting the hopes of the prisoners. Meanwhile, the woman who set him free accidently, Morgana, tries to find a way to stop him, aided by a young priest.
Languages: English Subtitles: No Subtitles
Keywords: Horror